Paradigm shift, metamorphosis of medical ethics, and the rise of bioethics - José Luiz Telles de Almeida; Fermin Roland Schramm (Cadernos de Saúde Pública)
Both the increasing incorporation of medical technology and new social demands (including those for health care) beginning in the 1960s have brought about significant changes in medical practice. This situation has in turn sparked a growth in the philosophical debate over problems pertaining to ethical practice. These issues no longer find answers in the Hippocratic ethical model. The authors believe that the crisis in Hippocratic ethics could be described as a period of paradigm shift in which a new set of values appears to be emerging. Beginning with the bioethics movement, the authors expound on the different ethical theories applied to medical practice and conclude that principlism is the most appropriate approach for solving the new moral dilemma imposed on clinical practice.